Energy transition: Utilization of solar energy as an energy source in smart building implementation as an effort to reduce the use of fossil energy - Irnawan, Rahman Fajar; Ismail , Yunita (Institute for Advanced Science Social, and Sustainable Future, 2024)
The increase in population certainly greatly affects the amount of existing energy consumption. Based on data taken by the Indonesia Energy Outlook 2019, in 2018 Indonesia has a total final energy consumption (not considering conventional energy) of around 40% of the energy used for the transportation sector, then 36% for industry, 16% for households, commercial and other sectors respectively 6% and 2% respectively. Then, in 2019 the total final energy consumption was 989.9 million Barrels of Oil Equivalent. Then the use of fossil energy has an impact on sustainable life because fossil energy is one of the contributors to carbon emissions on earth. The increase in emissions has an impact on the increase in GHS that has been felt by the earth, namely, the occurrence of very drastic climate changes, as well as affecting temperature rises of up to 3∘C. For this reason, it is necessary to have the potential for renewable energy by utilizing solar energy, namely the process of converting energy produced by solar radiation into electrical energy and efficient use of this energy using smart buildings.. Objectives: The aims of the journal is to know another potential energy sourced to reduce the fossil fuel uses. Method and results: Literature review.